Development of interactive learning media based on website chatbots on plant tissue material - Kulsum Musfiroh; S. Suharsono; Vita Meylani (Research and Development in Education (RaDEn), 2024)
The utilization of learning media is a valuable instrument in enhancing the learn-ing process, hence maximizing the attainment of learning objectives. The objec-tive of this study is to create an educational tool for biology instruction in the form of a website chatbot focused on plant tissue content. The research also seeks to evaluate the viability and efficacy of this tool when used by students. The pre-sent study used the ADDIE model, a widely recognized framework in the field of development research. This model encompasses five distinct stages, namely anal-ysis, design, development, implementation, and evaluation. The data utilized in this study was collected via interviews, questionnaires, and tests, and afterwards analyzed employing qualitative and quantitative descriptive statistical methods. The present study developed an educational tool in the form of a website chatbot focused on plant tissue materials. The validation process involved obtaining feed-back from media experts, material experts, and students. The assessment con-ducted by media experts resulted in a 91% rating, categorizing the chatbot as "very feasible." Similarly, the material expert's assessment yielded an 86.5% rat-ing, also falling into the "very feasible" category. Furthermore, students' respons-es indicated a 97.7% rating, categorizing the chatbot as "very feasible." Moreo-ver, based on the study conducted to evaluate the efficacy of learning media goods, the t-test findings revealed a significant difference between the pretest and post-test scores, as indicated by a Sig value (2-tailed) of 0.000, which is less than the predetermined significance level of 0.05. The mean gain for the website chat-bot learning media product is 0.77, falling inside the "high" category. This sug-gests that the product is very suited and effective as a learning medium.